1998
DOI: 10.1177/104063879801000222
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Peripheral Nerve Sheath Tumor in a Water Moccasin (Agkistrodon Piscivorus)

Abstract: Peripheral nerve sheath tumors (PNSTs) in domestic and wild animals are uncommon tumors that originate from cells that comprise the sheaths of peripheral nerves. One type of PNST originates from Schwann cells and is termed schwannoma. Two other types of cells, perineural cells and fibroblasts, are components of peripheral nerve sheaths and may give rise to tumors. These tumors, particularly the malignant variety, may have histologic patterns that closely mimic those of other fusiform tumors. Electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…Cells comprising the melanoma of the death adder Acanthopis antarcticus proved S-100-negative, using a polyclonal rabbit antibovine S-100 antibody (Kusewitt et al 1997). However, a malignant peripheral nerve-sheath tumor in the water moccasin Agkistrodon piscivorus was S-100-positive, whereas striated and smooth muscle cells were actin-positive, and nonmuscle mesenchymal cells were vimentin-positive, using commercially available antibodies from mammals (Ramis et al 1998). Immunohistochemical characterization of neoplastic cells in our sea turtles was negative.…”
Section: Discussionmentioning
confidence: 99%
“…Cells comprising the melanoma of the death adder Acanthopis antarcticus proved S-100-negative, using a polyclonal rabbit antibovine S-100 antibody (Kusewitt et al 1997). However, a malignant peripheral nerve-sheath tumor in the water moccasin Agkistrodon piscivorus was S-100-positive, whereas striated and smooth muscle cells were actin-positive, and nonmuscle mesenchymal cells were vimentin-positive, using commercially available antibodies from mammals (Ramis et al 1998). Immunohistochemical characterization of neoplastic cells in our sea turtles was negative.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding clinical presentation, the serpent presented signs mostly frequent observed in reptiles neoplasm, such as lethargy, dysphasia, anorexia and emaciation (Ramis et al 1998, Sykes & Trupkiewicz 2006. In general, the clinical manifestations are associated with the affected systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have found high recurrent and metastatic behavior of this and other neoplasms in snakes and other reptiles (Ramis et al 1998, Orós et al 2004, Hes et al 2007, Orós et al 2009, Salinas et al 2013, Sharpe et al 2013). On clinical examination, the fibrosarcomas are presented as small or large nodular mass and soft to firm consistency, which impair biological functions of some snakes such as swallowing.…”
Section: Introductionmentioning
confidence: 96%
“…Peripheral nerve sheath tumors have been reported rarely in snakes. 7,15 The histologic and electron microscopic morphology of the neoplastic cells in the current case were indicative of fibrosarcoma.…”
mentioning
confidence: 99%